2009
DOI: 10.1002/ange.200902090
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Detection of Living Bacteria at Ultralow Concentrations Using a Carbon Nanotube Based Potentiometric Aptasensor

Abstract: Keeping the doctor away: An aptamer attached to an electrode coated with single‐walled carbon nanotubes interacts selectively with bacteria (see picture). The resulting electrochemical response is highly accurate and reproducible and starts at ultralow bacteria concentrations, thus providing a simple, selective method for pathogen detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…After preparation of PTCA-functionalized chemical converted graphene (PTCA/CCG), NH 2 -modified aptamer strand was linked to PTCA/CCG via a carbodiimide-mediated wet-chemistry approach [12]. The resulting aptamer-PTCA nanocomposite was then used as nanoscale anchorage substrates to effectively capture cells on electrode surface via the specific binding between cell surface nucleolin and the aptamer AS1411.…”
Section: Introductionmentioning
confidence: 99%
“…After preparation of PTCA-functionalized chemical converted graphene (PTCA/CCG), NH 2 -modified aptamer strand was linked to PTCA/CCG via a carbodiimide-mediated wet-chemistry approach [12]. The resulting aptamer-PTCA nanocomposite was then used as nanoscale anchorage substrates to effectively capture cells on electrode surface via the specific binding between cell surface nucleolin and the aptamer AS1411.…”
Section: Introductionmentioning
confidence: 99%
“…18 The whole process of preparing specific enrichment media to separate, identify and count bacterial cells may take a few days after collecting the test sample. 19 Culture enables determination of antimicrobial susceptibilities, but in tropical environments is hampered by the need for stringent transport conditions to maintain specimen viability and a constant supply of reagents and electricity. 2 Serological techniques are simpler than isolation and direct detection of the pathogen, but usually require some days until a sufficient amount of antibodies is produced.…”
Section: Classical Methods Of Laboratory Diagnosismentioning
confidence: 99%
“…50 In view of the unavailability of fast, sensitive, selective, inexpensive and easy-to-use methods for detection and quantification of pathogenic bacteria cells, CNTs were used as efficient ion-to-electron transducers in potentiometric analysis for specific electrochemical detection of ultra-low levels of such targets. 19 Traditionally this is difficult without chemical labeling, as the receptor-bacteria interaction does not yield a measurable electrochemical signal; however, CNT-coupled aptamers can be used as highly selective receptors to detect such living cells as easily as measuring the pH value. Aptamers are specific nucleic acids that mimic antibodies in many applications, being comparable in affinity and specificity, while not requiring animal systems for their production, occurring rather in vitro.…”
Section: Nanobiotechnologymentioning
confidence: 99%
“…The main advantages of this detection system are simplicity due to the two-electrode system used in potentiometry, low cost, and real-time detection which make it highly valuable for different types of applications. Zelada-Guillén et al showed that the same strategy could be applied to quantify bacteria in real samples [17, 18]. The biosensing mechanism is thought to be based on the superficial restructuration of the aptamers lying onto the surface of the single-walled carbon nanotubes (SWCNTs) when the target analyte, displaying a very high affinity constant with the aptamers, enters in contact with them.…”
Section: Introductionmentioning
confidence: 99%